Genetics Influence Neurocognitive Performance at Baseline but Not Concussion History in Collegiate Student-Athletes. Issue 2 (March 2018) - Cochrane, Graham D.; Sundman, Mark H.; Hall, Eric E.; Kostek, Matthew C.; Patel, Kirtida; Barnes, Kenneth P.; Ketcham, Caroline J.
Abstract : Objective: This study investigates 4 single-nucleotide polymorphisms [Apolipoprotein E (APOE), APOE promoter, catechol-O-methyl transferase (COMT), and dopamine D2 receptor] that have been implicated in concussion susceptibility and/or cognitive ability in collegiate student-athletes. Design: Cross-sectional study. Setting: Neuroscience laboratory at Elon University. Participants: Two hundred fifty division I collegiate student-athletes (66 women, 184 men) from various sports. Intervention: All participants completed Immediate Postconcussion Assessment and Cognitive Testing (ImPACT) testing at baseline concussion testing and had a buccal swab taken for DNA for genotyping. Main Outcome Measures: Self-reported history of concussions and neurocognitive performance were taken from ImPACT. Results: Individuals carrying an ε4 allele in their APOE gene had a significantly slower reaction time ( P = 0.001). Individuals homozygous for the Val allele of the COMT gene showed significantly worse impulse control scores ( P = 0.014). None of the genotypes were able to predict self-reported concussion history in collegiate student-athletes. Conclusions: These results indicate that certain genotypes may influence performance on cognitive testing at baseline and that the APOE genotypes may not influence concussion susceptibility as suggested by past studies.